Lipophosphoglycan blocks attachment of Leishmania major amastigotes to macrophages. - Kelleher, M (1995)
Promastigotes of the intracellular protozoan parasite Leishmania major invade mononuclear phagocytes by a direct interaction between the cell surface lipophosphoglycan found on all Leishmania species and macrophage receptors. This interaction is mediated by phosphoglycan repeats containing oligomers of beta (1-3)Gal residues specific to L. major. We show here that although amastigotes also use lipophosphoglycan to bind to both primary macrophages and a cell line, this interaction is independent of the beta (1-3)Gal residues employed by promastigotes. Binding of amastigotes to macrophages could be blocked by intact lipophosphoglycan from L. major amastigotes as well as by lipophosphoglycan from promastigotes of several other Leishmania species, suggesting involvement of a conserved domain. Binding of amastigotes to macrophages could be blocked significantly by the monoclonal antibody WIC 108.3, directed to the lipophosphoglycan backbone. The glycan core of lipophosphoglycan could also inhibit attachment of amastigotes, but to a considerably lesser extent. The glycan core structure is also present in the type 2 glycoinositolphospholipids which are expressed on the surface of amastigotes at 100-fold-higher levels than lipophosphoglycan. However, their inhibitory effect could not be increased even when they were used at a 300-fold-higher concentration than lipophosphoglycan, indicating that lipophosphoglycan is the major macrophage-binding molecule on amastigotes of L. major. In the presence of complement, the attachment of amastigotes to macrophages was not altered, suggesting that lipophosphoglycan interacts directly with macrophage receptors.